C2N-graphene supported single-atom catalysts for CO2 electrochemical reduction reaction: mechanistic insight and catalyst screening. Issue 32 (1st August 2018) - Cui, Xudong; An, Wei; Liu, Xiaoyang; Wang, Hao; Men, Yong; Wang, Jinguo
Abstract : Mechanistic insight and catalyst screening of C2 N-graphene supported single-atom catalysts for CO2 electrochemical reduction reaction are provided from a theoretical perspective. Abstract : Single-atom catalysts (SACs) have emerged as an excellent platform for enhancing catalytic performance. Inspired by the recent experimental synthesis of nitrogenated holey 2D graphene (C2 N-h2D) (Mahmood et al., Nat. Commun., 2015, 6, 6486–6493), we report density functional theory calculations combined with computational hydrogen electrode model to show that C2 N-h2D supported metal single atoms (M@C2 N) are promising electrocatalysts for CO2 reduction reaction (CO2 RR). M confined at pyridinic N6 cavity promotes activation of inert OCO bonds and subsequent protonation steps, with *COOH → *CO → CHO predicted to be the primary pathway for producing methanol and methane. It is found that *CO + H + + e − → *CHO is most likely to be the potential determining step; breaking the scaling relation of *CO and *CHO binding on M@C2 N SACs may simply be a rare event that is sensitively controlled by the detailed geometry of the adsorbate. Among twelve metals screened, M@C2 N SACs where M = Ti, Mn, Fe, Co, Ni, Ru were identified to be effective in catalyzing CO2 RR with lowered overpotentials (0.58 V–0.80 V).